A bi‐centric experience of extracorporeal carbon dioxide removal (ECCO2R) for acute hypercapnic respiratory failure following allogeneic hematopoietic stem cell transplantation. Issue 8 (4th May 2021) - Wohlfarth, Philipp; Schellongowski, Peter; Staudinger, Thomas; Rabitsch, Werner; Hermann, Alexander; Buchtele, Nina; Turki, Amin T.; Tzalavras, Asterios; Liebregts, Tobias
Abstract: Acute respiratory failure (ARF) is the main reason for ICU admission following allogeneic hematopoietic stem cell transplantation (HSCT). Extracorporeal CO2 removal (ECCO2 R) can be used as an adjunct to mechanical ventilation in patients with severe hypercapnia but has not been assessed in HSCT recipients. Retrospective analysis of all allogeneic HSCT recipients ≥18 years treated with ECCO2 R at two HSCT centers. 11 patients (m:f = 4:7, median age: 45 [IQR: 32‐58] years) were analyzed. Acute leukemia was the underlying hematologic malignancy in all patients. The time from HSCT to ICU admission was 37 [8‐79] months, and 9/11 (82%) suffered from chronic graft‐versus‐host disease (GVHD) with lung involvement. Pneumonia was the most frequent reason for ventilatory decompensation ( n = 9). ECCO2 R was initiated for severe hypercapnia (Pa CO2 : 96 [84‐115] mm Hg; pH: 7.13 [7.09‐7.27]) despite aggressive mechanical ventilation (invasive, n = 9; non‐invasive, n = 2). ECCO2 R effectively resolved blood gas disturbances in all patients, but only 2/11 (18%) could be weaned off ventilatory support, and one (9%) patient survived hospital discharge. Progressive respiratory and multiorgan dysfunction were the main reasons for treatment failure. ECCO2 R was technically feasible but resulted in a low survival rate in our cohort. A better understanding of the prognosis of ARF in patients with chronic GVHD and lung involvement is necessary before its use can be reconsidered in this setting. Abstract : ECCO2 R is technically feasible but results in low survival in patients with chronic GVHD and lung involvement after hematopoietic stem cell transplantation. Further study on the prognosis of respiratory failure in these patients is necessary before ECCO2 R can be reconsidered in this setting